Pkm Pemanfaatan Aplikasi Point Of Sale (Pos) Pada Pos Coffee Berbasis Digital - Agustina Simangunsong; Adli Abdillah Nababan (Cv. Utility Project Solution, 2023)
At the moment, Pos Coffee still uses a conventional system for food or drink orders, where servers use pen and paper to jot down customer orders. This service system has become less effective and efficient due to an increasing number of customers. Additionally, the pantry area is not well-organized regarding the management of food ordering queues, making it difficult to process orders efficiently. Furthermore, daily and monthly financial reporting processes are still done conventionally, leading to numerous errors, duplicated data, difficulty in searching and storing the growing volume of data, and frequent delays in providing accountability reports to superiors. Based on these issues, there is a need to develop a digital-based application called Point Of Sale (POS). Point of Sale (POS) is a system that facilitates transactions, including the use of cash register machines connected to cloud computing, ensuring that all store transactions are well recorded. The purpose of this community service at Pos Coffee is to train staff and employees of Kopikuni to effectively and correctly implement the digital-based POS application, especially within the environment of Pos Coffee.